The Behavioural Response of Humpback Whales (Megaptera novaeangliae) to a 20 Cubic Inch Air Gun - Dunlop, R.; Noad, M.; McCauley, Robert; Kniest, E.; Paton, D.; Cato, D. (EUROPEAN ASSOC AQUATIC MAMMALS, 2015)
Seismic surveys are widely used for exploration for oil and gas deposits below the sea floor. Despite concern they may have an impact on whale behaviour, our knowledge of marine mammal responses is limited. In the first of a series of experiments (the last one involving a full seismic array), this study tested the response of migrating humpback whale (Megaptera novaeangliae) groups to a 20 cubic inch air gun. Experiments were carried out during the southward migration of humpback whales along the east coast of Australia. Groups of whales were focally followed from land stations and/or small boats with observations before, during, and after exposure to a vessel towing the air gun. The source vessel moved either eastwards across the migratory flow or northwards into the migratory flow. In total, there were 18 control trials (where the source vessel ran the compressor and towed the air gun without it firing; n = 35 whale groups) and 16 active trials (where the air gun was firing every 11 s; n = 32 whale groups). The air gun source level was 199 dB re 1 μPa2.s (Sound Exposure Level [SEL]) at 1 m, and SELs received by the whales varied from 105 to 156 dB re 1 μPa2.s (modal value 128 dB re μPa2.s) for SELs at least 10 dB above the background noise (measured as dB re 1 μPa). Other baseline groups were focal followed when there was no source vessel in the area (n = 25). Results suggested that humpback whale groups responded by decreasing both dive time and speed of southwards movement though the response magnitude was not found to be related to the proximity of the source vessel, the received level of the air gun, the tow path direction, or the exposure time within the during phase. There was no evidence of orientation of the groups towards, or away from, the source vessel in the during phase. Interestingly, this behavioural response was found in the control trials as well as the active trials suggesting a response to the source vessel.